2020
DOI: 10.1126/sciadv.aay4312
|View full text |Cite
|
Sign up to set email alerts
|

Resolving hydrogen atoms at metal-metal hydride interfaces

Abstract: Hydrogen as a fuel can be stored safely with high volumetric density in metals. It can, however, also be detrimental to metals causing embrittlement. Understanding fundamental behavior of hydrogen at atomic scale is key to improve the properties of metalmetal hydride systems. However, currently, there is no robust technique capable of visualizing hydrogen atoms. Here, we demonstrate that hydrogen atoms can be imaged unprecedentedly with integrated differential phase contrast, a recently developed technique per… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 53 publications
0
66
0
Order By: Relevance
“…STEM images of γ‐TiH/α‐Ti interface using f) HAADF, g) ABF, and h) iDPC modes with simulated images as insets. Reproduced with permission 385. Copyright 2018, Cornell University.…”
Section: Materials Science Applications and Discoveriesmentioning
confidence: 99%
See 2 more Smart Citations
“…STEM images of γ‐TiH/α‐Ti interface using f) HAADF, g) ABF, and h) iDPC modes with simulated images as insets. Reproduced with permission 385. Copyright 2018, Cornell University.…”
Section: Materials Science Applications and Discoveriesmentioning
confidence: 99%
“…Recently, atomic‐resolution imaging of hydrogen have been realized at the interface between the hexagonal close‐packed titanium and face‐centered tetragonal titanium monohydride by using and Cs‐corrected iDPC‐STEM (Figure 22c–h). 385 The ideal interface between γ‐TiH and α‐Ti could have three potential models of atomic arrangements (Types I–III; Figure 22e). Comparing the images that are obtained from HAADF, ABF, and iDPC, it is concluded that iDPC has superior performance than ABF and HAADF regarding the detection of light elements 385.…”
Section: Materials Science Applications and Discoveriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, ADF images are dominated by cation contrast that precludes detailed detection and quantification of light elements such as oxygen. Recently, annular bright field (ABF) 27,28 and integrated differential phase contrast (iDPC) 29,30 STEM techniques have been developed to overcome these challenges. While iDPC can detect the cation and oxygen atom column positions, as shown in Figure 1a, it too has a major drawback: the image contrast lacks the atomic number interpretability of ADF STEM.…”
mentioning
confidence: 99%
“…Here, we investigate the structural and chemical origins of relaxor ferroelectric properties in 10,and 30). Through a combination of ADF and iDPC aberration corrected STEM, the projected positions of cation and anion sub-lattices are used to measure the subtle features of nanoscale polarization in these materials.…”
mentioning
confidence: 99%